2000
DOI: 10.1034/j.1399-3003.2000.16b07.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in peak expiratory flow indices as a proxy for changes in bronchial hyperresponsiveness

Abstract: Guidelines for asthma management advocate home peak expiratory flow (PEF) monitoring. It is commonly stated that PEF variability is a good proxy of bronchial hyperresponsiveness (BHR), a hallmark of asthma. However, this has hardly been tested longitudinally, as required to monitor asthma. This study assesses which PEF index correlates best with BHR longitudinally and whether the correlation improves when correcting PEF values for the known nonlinearity of mini-Wright PEF meters.Every 6 months, for a period of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Thus, improvement through training extended beyond patients' perception of their disease to a somatic outcome measure central to the pathophysiology of asthma. Although the relationship between PEF variability and airway hyperresponsiveness has been debated (Douma, Kerstjens, Roos, et al, 2000;Reddel, Salome, Peat, et al, 1995), such findings are compatible with prior findings of a negative correlation between pCO 2 and hyperresponsiveness to methacholine challenge (Osborne et al, 2000). It is likely that additional benefits of an adjunctive breathing training will be less apparent in basal lung function (or only be visible in more direct measures of airway obstruction) than in a reduction of fluctuations in symptoms.…”
Section: Discussionsupporting
confidence: 78%
“…Thus, improvement through training extended beyond patients' perception of their disease to a somatic outcome measure central to the pathophysiology of asthma. Although the relationship between PEF variability and airway hyperresponsiveness has been debated (Douma, Kerstjens, Roos, et al, 2000;Reddel, Salome, Peat, et al, 1995), such findings are compatible with prior findings of a negative correlation between pCO 2 and hyperresponsiveness to methacholine challenge (Osborne et al, 2000). It is likely that additional benefits of an adjunctive breathing training will be less apparent in basal lung function (or only be visible in more direct measures of airway obstruction) than in a reduction of fluctuations in symptoms.…”
Section: Discussionsupporting
confidence: 78%
“…Monitoring of PEF variability alone is not able to identify the deterioration in FEV1 as well as the provocative dose of histamine causing a 20% fall in FEV1 in patients on long-term inhaled corticosteroids, and the increase in symptom score is not always related to an increase in PEF variability [53]. Similar poor correlation is found when, within each subject, PEF variability and BHR are correlated longitudinally [54]. Thus, PEF variability may represent something different from symptoms and BHR, and PEF evaluation may be helpful in optimising asthma control.…”
Section: Peak Expiratory Flow Bronchial Hyperresponsiveness and Sympmentioning
confidence: 62%
“…5 Although many consensus statements recommend measuring PEF variability as a surrogate of bronchial hyperresponsiveness, only few cross-sectional studies yield some support to this advice 1,4,15 and, by contrast, some other works showed poor agreement between PEF variability and airway hyperresponsiveness or asthma diagnosis. [20][21][22][23][24] These contrasting reports, and the discrepancy between the clinical and functional patient classifications found in our study, pointed out that the usefulness of PEF variability will remain low as long as the timing for PEF measurements is not well standardized and, more important, comprehensive knowledge about how to interpret it can be gained.…”
Section: Discussionmentioning
confidence: 81%